Increased production of interleukin 1 beta and hepatocyte growth factor may contribute to foveolar hyperplasia in enlarged fold gastritis. Issue 6 (December 1996) - Yasunaga, Y; Shinomura, Y; Kanayama, S; Higashimoto, Y; Yabu, M; Miyazaki, Y; Kondo, S; Murayama, Y; Nishibayashi, H; Kitamura, S; Matsuzawa, Y
Abstract : BACKGROUND AND AIMS: It has been reported that eradication of Helicobacter pylori improves fold width in H pylori associated enlarged fold gastritis. The aim of this study was to clarify the mechanism of fold thickening in this condition. PATIENTS AND METHODS: In eight patients with enlarged fold gastritis and 13 patients without enlarged folds, the presence of H pylori infection, inflammatory infiltrates, mucosal plasia, and epithelial cell proliferation in the body mucosa were investigated, and production of transforming growth factor alpha (TGF alpha), hepatocyte growth factor (HGF), and interleukin 1 beta (IL 1 beta) was determined by a competitive reverse transcription/polymerase chain reaction method and in vitro short-term culture of biopsy specimens. RESULTS: In the patients with enlarged fold gastritis, inflammatory infiltrates including macrophages increased with H pylori colonisation in the body. Foveolar thickness and proliferating cell nuclear antigen (PCNA) labelling index were increased. Messenger RNA levels of HGF, but not TGF alpha, were increased, and release of HGF and IL 1 beta was increased. HGF release, which was positively correlated with IL 1 beta release and foveolar thickness, decreased in the presence of IL 1 receptor antagonist. After eradication of H pylori, inflammatory infiltrates, IL 1 beta and HGF release decreased with concomitant decreases in PCNA labelling index, foveolar thickness and fold width. CONCLUSIONS: Increased IL 1 beta and HGF production caused by H pylori infection may contribute to fold thickening of the stomach by stimulating epithelial cell proliferation and foveolar hyperplasia in patients with enlarged fold gastritis.